Implementation of PXP in Developing a Website for Computer Sales and Services - Maulana Bryan Syahputra; Nur Cahyo Wibowo; Rizka Hadiwiyanti (bit-Tech, 2025)
Technology is crucial for enhancing competitiveness and service quality for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. However, many MSMEs, including CV. Tecomp’99, a computer sales and repair company, still rely on manual processes, resulting in inefficiencies and reduced customer satisfaction. This study designs and implements an integrated web-based sales and service information system for CV. Tecomp’99 using the Personal Extreme Programming (PXP) methodology, a lightweight adaptation of Extreme Programming for individual developers. PXP was applied iteratively through requirement gathering, planning, implementation, testing, refactoring, and retrospectives. The system was developed using Laravel, Tailwind CSS, and MySQL, and validated through 67 test scenarios. Development was completed in four iterations, with 19 user stories implemented and a total of 71 story points completed in 63 working days, demonstrating stable velocity and reliable estimation. The resulting system integrates product sales, service order management, payment processing, reporting, live chat, and service tracking, improving workflow efficiency by 20% and reducing order processing time by 30%. These improvements are backed by measurable outcomes from testing and user feedback. Findings indicate that PXP is an effective framework for small-scale projects in MSMEs, supporting iterative development under resource constraints. Future work should include integrating AI-driven analytics for decision-making, enhancing mobile platform access, and developing customer feedback loops for continuous system improvement.